Sociodemographic characteristics and ethnic prejudice in students in Banja Luka - Haneš, Olja (Primenjena psihologija, 2012)
This research is trying to determine correlations between sociodemographic characteristics and expression of ethnic prejudice in students enrolled at the Faculty of Philosophy in Banja Luka. It also explores the problem of appearance of social distance between students and certain ethnic groups. The objective of this research was to gain an insight into some of possible risk factors that cause the appearance of ethnic prejudice. 150 students from different study groups from the Faculty of Philosophy were participants in this research. The following measuring instruments were used: The questionnaire of sociodemographic characteristics, the Scale of ethnic distance, and the Scale of ethnic stereotypes. Associations between sociodemographic characteristics (such as age, sex, nationality, mother’s education level, father’s education level, parents’ monthly income, ethnic uniformity of parents, relatives and friends), social distance and stereotypes in students were examined. Finally, methodological, and theoretical issues were discussed.